Hubungan Antara Kebiasaan Sarapan Pagi dan Prestasi Belajar Anak Sekolah Dasar - Iqbal, Fahmi Maulana, dr. N. Juni Triastuti, M. Med. Ed, dr. Sri Wahyu Basuki, M.Kes (2015)
Background : Education is one of the important factors for improving the quality of the nation's future . Attainment of the objectives of the national education seen from a child's learning achievements that have been achieved . High academic achievement indicated good knowledge anyway. Learning achievement of children is determined by internal and external factors. Breakfast is recommended to influence the improvement of learning in children in terms of behavioral , cognitive , and learning achievement of children in school. Objective : The goal of the research was to find out the relationship between breakfast habits and academic performance at children of primary school. Methods : Design studied using observational analytic researched with cross sectional approach. This study was conducted in January 2015 in SD Negeri 1 Karangasem Surakarta with the sample of children in grades 3 through grade 6 as many as 161 children selected by simple random sampling technique to obtained a sample of 80 children. Hypothesis test used is the chi-square test with SPSS 17.0 for Windows. Results : The research result that showed the value of p=0.045 for the relationship between breakfast habits and academic performance at children of primary school, where p<0.05. Conclusion : There are relationship between breakfast habits and academic performance at children of primary school.